"Out of Sight, Out of Mind?": The Role of Physical Stressors, Cognitive Appraisal, and Positive Emotions in Employees' Health. Issue 1 (January 2018) - Kożusznik, Małgorzata W.; Peiró, José M.; Soriano, Aida; Navarro Escudero, Miriam
This study analyzes the mediating role of the appraisal of environmental stressors in the relationship between physical characteristics in the offices and health symptoms. It also studies the moderating role of positive emotions in the relationship between physical characteristics and the appraisal of environmental stressors using a diary study on 59 office workers ( n = 432 time points) and sensor data. The results show that the appraisal of environmental stressors mediates the relationship between physical office characteristics and health symptoms, emphasizing the important link of stress appraisal in the stressors–strain relationship. The results also show that positive emotions moderate the relationship between the sound level and the appraisal of noise, supporting the fact that emotions can have an impact on people's appraisals. The contributions of this study are the objective measurement of physical stressors in offices, along with their appraisals by the office users, using the diary study design.